DYNAMICS OF GROWTH AND DEVELOPMENT OF CALENDULA OFFICINALIS PLANTS (CALENDULA OFFICINALIS L.) BY DURATION AND PHASES OF VEGETATION IN THE CONDITIONS OF THE RIGHT-BANK FOREST STEPPE OF UKRAINE - Падалко, Тетяна (SWorldJournal, 2024)
The article, based on the results of scientific research in 20018-2023, highlights the biological features and medicinal potential of the calendula plant (Calendula officinalis L.) in the conditions of the Right Bank Forest Steppe of Ukraine. It was esta